Intellectual capital and financial performance of Portuguese tourism sector - Silva, Lurdes (2022)
According to the literature, intellectual capital is a critical element of value creation in organizational performance that is capable of contributing to sustainable and higher financial income. The objective of this paper is to identify the added value and efficiency of intellectual capital in its three dimensions - (i) human capital, (ii) structural capital and (iii) relational capital - in the tourism sector and assess its impact on organizational performance. The data was obtained from the Simplified Enterprise Information System (IES) based on the Iberian Balance Analysis System (SABI). The study was conducted with a sample of balance sheets and financial reports of 46,951 Portuguese companies in the tourism sector between 2007 and 2016. The results showed that all dimensions of intellectual capital have a positive and significant impact on the business performance of the Portuguese tourism sector. Human capital is the most effective dimension of intellectual capital and value added. The application of the Value Added Intellectual Coefficient (VAIC) model provides practical implications for the management and valorization of intellectual capital. Therefore, the empirical results with the present analysis are relevant for the future strategy for the development of the tourism sector in Portugal.